Government healthcare financing and dwindling oil prices: Any alternatives for OPEC countries? - Salem Al Mustanyir (Cogent Economics & Finance, 2023)
Crude oil is one of the sources by which budgets are financed in OPEC countries. However, the fall in oil prices in 2014 put their governments' finances under significant pressure. Healthcare was one of the sectors experiencing fiscal strain. This study examined the effect of a fall in oil prices on healthcare financing in eight OPEC countries and whether such financing has shifted away from the dependence on oil. Quantitative healthcare expenditure data from the WHO covering the period from 2003 to 2019 were evaluated using a comparison of means Welch's t-test. The result showed that government healthcare expenditure in Iran, Venezuela, and Kuwait increased in the period post-2014 compared to the expenditure after 2008 and 2002, suggesting that these countries succeeded in shielding such spending against the fall in oil prices. By contrast, the United Arab Emirates, Saudi Arabia, Iraq, Nigeria, and Algeria did not, highlighting that they have not yet moved from dependence on oil. With the economic uncertainty caused by oil fluctuations, global political and economic developments, and the world transitioning to green energy, oil-dependent countries should free their governments' healthcare expenditure from dependence on such sources of funding. Furthermore, they should not focus on temporary plans by shifting the burden to private spending at a time of falling oil prices, but to utilize different financing approaches.
Keywords: H51; H61; H72; H75; I18; 330; dependence on oil; fall in oil prices; financing challenges; healthcare expenditure; OPEC countries